Synthesis and characterization of functionalized ordered mesoporous silica Mcm-41 with macrocyclic compounds for the adsorption of organotin compounds / Alahmadi Sana Mohammad T - Mohammad T, Alahmadi Sana (2014)
The work presented in this thesis consists of two parts, focusing on the synthesis and characterization of modified mesoporous MCM-41 with macrocyclic compounds and their application as an adsorbent for organotin compounds removal. The first part of work dealt with the modification of mesoporous silica MCM-41 with macrocyclic compound via a post-synthesis grafting method with calix[4]arene, calix[4]arene sulfonate, para-tertbutylcalix[ 4]arene and β-cyclodextrin by using toluene-2,4-diisocyanate as the coupling agent (MCM-TDI-C4, MCM-TDI-PC4, MCM-TDI-C4S and MCM-TDI-β-CD) in the first method, and also by using toluene-2,4-diisocyanate and organosilane (3-chloropropyl triethoxysilane-ClPTS) as coupling agents in the second method (MCM-PS-TDI-C4, MCM-PS-TDI-PC4, MCM-PS-TDI-C4S, and MCM-PS-TDI-β-CD). Different techniques such as infrared (FTIR), elemental analysis, thermal gravimetric analysis (TGA) and X-ray powder diffraction (XRD) were used to confirm the production of the desired products. The surface area, pore size and pore size distribution were determined using the surface area analysis (BET) method. The functionalized mesoporous materials with calix[4]arene derivatives and toluene diisocyanate as coupling agent (MCM-TDI-C4, MCM-TDI-PC4 and MCM-TDI-C4S) possessed high surface areas, large pore sizes and narrow pore size distributions compared to other synthetic materials. The screening study of the adsorption of organotin compounds (tributyltin TBT, triphenyltin TPT and dibutyltin DBT) onto prepared materials showed that functionalized mesoporous materials with calix[4]arene derivatives by using toluene-2,4-diisocyanate as coupling agent materials have a higher adsorption capacity compared to the other prepared materials. A percentage removal for TBT, TPT and DBT from aqueous solution of 98, 95 and 97 %, respectively, by MCMTDI- PC4 were produced in this study. Isotherms, kinetics and thermodynamics of the adsorption of TBT, TPT and DBT on the prepared mesoporous materials (MCM-TDI-C4, MCM-TDI-PC4 and MCM-TDI-C4S) were investigated. The effect of operating parameters, such as contact time, adsorbate initial concentration, initial pH and temperature were studied. The adsorption capacity was affected by these parameters. The contact time of adsorbent reached equilibrium within 2 h. The maximum adsorption capacity of TBT, TPT and DBT occurred at pH 6. It was found that the maximum adsorption capacities of TBT, TPT and DBT were 16.42, 19.31 and 18.82 mg/g, respectively, for the prepared material MCM-TDI-PC4. Equilibrium modelling of the adsorption isotherm showed that adsorption of those three organotin compounds was able to be described by the threeparameter model better than the two-parameter model. The empirical kinetic data of the adsorption of TBT, TPT and DBT by prepared materials were well described by the second order model. Values of ΔG° indicate that the adsorption of TBT, TPT and DBT onto all adsorbents were spontaneous processes.